ANALISIS TANTANGAN YANG DIHADAPI OLEH SISWA DI SMPI DARUDDA'WAH PUNGGUR KECIL, KALIMANTAN BARAT, DALAM PEMBELAJARAN BAHASA INGGRIS - Nizarrahmadi, Nizarrahmadi; Al ghazali, Reneldy (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This study aims to explore and examine the challenges experienced by ninth-grade students at SMPI Darudda’wah in learning English during the 2023 academic year. It also seeks to develop effective learning strategies to boost students' motivation and interest in the subject. A qualitative research approach was employed, involving classroom observations, student interviews, and analysis of relevant documents. Five ninth-grade students participated in interviews, which focused on their understanding of the material, as well as their motivation and interest in learning English. The findings reveal differing levels of comprehension, motivation, and enthusiasm among students. Contributing factors include feelings of anxiety, low self-confidence, and the burden of extracurricular commitments. The study identifies practical learning activities, enhanced teacher involvement, and curriculum adjustments as promising strategies to support and improve English language learning at SMPI Darudda’wah Punggur Kecil.